Covid-19 Patient Satisfaction Analysis Reviewing from the Quality of Health Services and the Performance of Health Personnel - Irsyad Herminofa; Rahmania Ambarika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Satisfaction is a feeling of pleasure or disappointment that comes from comparing his impression of the service or result and his expectations. Satisfaction with patients is a pleasant emotional attitude at work. This attitude can be reflected in work morale, discipline, and work performance. In order to achieve the maximum level of patient satisfaction in carrying out tasks, one will always face the given factors that can affect patient satisfaction. So that health service institutions can create conditions that can encourage or improve services to develop and improve their abilities and skills optimally (Arief and Alfarizy 2019). Patient satisfaction is related to fulfilling one's needs with a positive attitude from health workers, which includes feelings and behavior towards their work through assessing one job as a sense of appreciation in achieving a solid job value. (Astari, Noviantani, and Simanjuntak 2021). The type of research used in this research is quantitative research with correlation studies. The sample in this study which was taken using a simple random sampling technique, were Covid-19 patients treated at the Covid-19 Isolation Home UPT Gondang Health Center, totaling 160 respondents. The study was conducted using a questionnaire and analyzed using a logistic regression test. The relationship between service quality and staff performance on patient satisfaction shows that based on the results of logistic regression tests, the dominant variable that affects patient satisfaction is staff performance. This can be seen from the largest Exp. B (OR) value, which is 320, means that the performance of good health workers will affect reasonable patient satisfaction. Research reveals that patient satisfaction during treatment is not only focused on service quality but can be expressed in the form of health care services. The reliable performance will also foster satisfaction for the patients they treat.